2020
DOI: 10.3390/ma13020429
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Residual CaSO4 in Clinker on Properties of High Belite Sulfoaluminate Cement Based on Solid Wastes

Abstract: The high belite sulfoaluminate cement (HBSAC) containing CaSO4, and without CaSO4, based on solid wastes were successfully prepared from petroleum coke desulfurization slag (PCDS), fly ash (FA), carbide slag (CS), and bauxite (BX). The mineral composition of clinkers after different calcination history were investigated by X-ray fluorescence (XRF), X-ray diffraction (XRD)/Quantitative X-ray diffraction (QXRD), and scanning electron microscopy (SEM), so as to determine the calcination temperatures. The differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Ma et al 52 studied the effect of FA on the performance of SAC and came to the same conclusion that FA shortens the coagulation time by decreasing the compressive strength and inhibiting the drying shrinkage of cement. Through X-ray diffraction and scanning electron microscopy, Su et al 53 and Zhuo et al 54 found that the effect of FA on SAC properties mainly depends on AFt generation. FA decreases the compressive strength of SAC by inhibiting the rate and amount of Aft generation.…”
Section: Modified Cement-based Materials With Sac As the Basementioning
confidence: 99%
“…Ma et al 52 studied the effect of FA on the performance of SAC and came to the same conclusion that FA shortens the coagulation time by decreasing the compressive strength and inhibiting the drying shrinkage of cement. Through X-ray diffraction and scanning electron microscopy, Su et al 53 and Zhuo et al 54 found that the effect of FA on SAC properties mainly depends on AFt generation. FA decreases the compressive strength of SAC by inhibiting the rate and amount of Aft generation.…”
Section: Modified Cement-based Materials With Sac As the Basementioning
confidence: 99%
“…The compressive strength of HT-BYF-1200 mortar begins low at early age (2 days of hardening), compared to DM-BYF-1300 and control mortars, despite the rapid hydration of this cement as deduced from XRPD and thermal analysis results. This was due to the rapid formation of ettringite after 1 day of hardening giving high amount of this expansive compound (Table 8) causing many cracks within cement matrix [11,51] as shown in Figure 13. A self repair of the mortar matrix with cracks sealing due to the crystallization of ettringite and the production of C-S-H resulting from β-C2S hydration, were able to catch up the development of resistance with hardening age of HT-BYF-1200 mortar [40,[51][52][53] .…”
Section: Compressive Strength Evolution Of the Synthesized Cement Mor...mentioning
confidence: 99%
“…This was due to the rapid formation of ettringite after 1 day of hardening giving high amount of this expansive compound (Table 8) causing many cracks within cement matrix [11,51] as shown in Figure 13. A self repair of the mortar matrix with cracks sealing due to the crystallization of ettringite and the production of C-S-H resulting from β-C2S hydration, were able to catch up the development of resistance with hardening age of HT-BYF-1200 mortar [40,[51][52][53] . DM-BYF-1300 cement mortar achieved high resistance at early hardening age (15 MPa at 2 days) (Figure 13), due to the low ettringite content compared to HT-BYF-1200 (Tables 8, 9), avoiding the excessive formation of cracks within the mortar matrix.…”
Section: Compressive Strength Evolution Of the Synthesized Cement Mor...mentioning
confidence: 99%
“…The kinetic of hydration of the ye'elimite phase is very fast and almost independent of the amount of anhydrite or water-to-cement ratio [18] but it can be influenced by the presence of other aluminates [19]. In addition, the sulphate content and type affect the kinetic of silicates in general [20,21], and belite in particular [18,22], by retarding their hydration with the increase in sulphate dissolution. The decrease of water-to-cement (w/c) ratio is a positive strategy to enhance mechanical strengths [23,24] but its effect on hydration kinetics is still not fully understood, especially the effect on phase assemblage and microstructural development [25].…”
Section: Introductionmentioning
confidence: 99%